Recovery of smectite and kaolinite from pottery clay via supercentrifugation technique - Ambait, Johanna Michelle S.
Clay is a naturally occurring nanomaterial. Commonly, it is used as a pottery material in the Philippines, particularly in San Nicolas, Ilocos Norte because of its high plasticity, small particle size, and the ability to harden when fired. At the advent of nanotechnology, upgraded natural clay material (nanoclay) has a potential to be used as an advance material. Some researchers have used nanoclay to form nanocomposites with the applications in different industries such as drug carriers and fillers in cosmetics, an adsorbent for waste water treatment and for energy storage applications. In the interest of adding value to our country's clay usage, this study aims to recover nanoclay from San Nicolas pottery material. The separation of nanoclay from non-clay minerals in soil was investigated by using supercentrifugation. A 2^2 factorial experiment was used to assess effects of the material and equipment settings on the quality of the recovered nanoclay. The clay sluny was prepared by wet milling and then wet sieving to screen off particle sizes greater than the nozzle size of the supercentrifuge. High and low levels of the factors were explored. The material property factors were percent solid loading and particle size while the equipment propelties were speed and nozzle size. Significant factors were evaluated through the use of statistical techniques for the analys is of variance of the yield of recovered nanoclay and quality of the product determined usIng X-ray diffraction analysis, i.e. using method of known addition, Srodon's MIF method, and integrated intensity differences. Only the percent solid loading was significant having a p-value of 3.778 x 10^-8 for the material factors while both speed and nozzle size were significant for equipment factors with p-value 7.995 x10^-6 and 2.599 x 10^-4, respectively. Correlations between the material and equipment factors show that nozzle size and percent solid loading are negatively correlated while speed and percent solid loading are positively correlated. San Nicolas raw clay contained an average of 17.07% smectite, 7.6225% kaolinite and 75.3075% non-clay soil minerals. After one cycle of supercentrifugation, highest yield was obtained by low percent solid loading, high nozzle size, and low speed settings with an average yield of 6.55%. A continuous gravity feeding process for the supercentrifugation teclmique was established and shown to obtain high purity nanoclay material containing 64.9% smectite and 13.3% kaolinite.